Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate, sodium-ion battery and power-related equipment
By reacting with organic acid and lithium hydroxide on the surface of the positive electrode material of the sodium ion battery to form sodium replenishing agent and water, and introducing trace lithium through liquid phase ion exchange, the problem of residual alkali on the surface of the positive electrode material particles of the O3 structure is solved, and the battery is improved Structural stability and electrochemical properties.
Patent Information
- Application Number
- CN202411665606.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
AI Technical Summary
There is a large amount of residual alkali on the surface of the positive electrode material of the existing O3 structure sodium ion battery, which leads to side reactions and gel phenomena, affecting battery performance and process costs.
By mixing and sintering the precursor and sodium source, a positive electrode material is obtained, and then mixed with organic acid and lithium hydroxide and grinding. The organic acid reacts with residual alkali to form a sodium replenishing agent and water. The dissolved lithium ions are introduced into microscopic amounts through liquid phase ion exchange Lithium relieves oxygen-oxygen repulsion and improves structural stability.
This method not only generates sodium supplementation agents in situ on the surface of the positive electrode material, but also reduces the consumption of active sodium, but also inhibits slip phenomenon by introducing lithium ions, improving electrochemical performance and material utilization efficiency.
Smart Images

Figure CN119495739A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and electrical equipment. Background Art
[0002] Lithium-ion batteries have been widely used in the 3C, power battery and energy storage markets due to their high energy density and long cycle life. However, the abundance of lithium resources is limited and it is difficult to mine. With the continuous consumption of lithium resources, new chemical systems are urgently needed to supplement the application market of lithium-ion batteries. Sodium-ion batteries work in the same principle as lithium-ion batteries, so sodium-ion batteries (SIBs) are considered to be a promising competitor for the next generation of rechargeable batteries.
[0003] In the SIBs system, Na + The migration of active sodium forms an irreversible reaction on the surface of the negative electrode to form a solid electrolyte interface (SEI) film, which greatly consumes the available active sodium resources. Therefore, the initial coulombic efficiency (ICE) and energy density of sodium-ion batteries are adversely affected, posing challenges to the development and widespread adoption of SIBs. In order to balance the consumption of active sodium, a common practice is to incorporate excess positive electrode materials into the entire battery. However, this method significantly reduces the utilization efficiency of the positive electrode material and the overall energy density of the battery. In addition, the existing sodium supplements Na3P and NaN3 have flammability and explosiveness problems, making them difficult to apply in industrial production.
[0004] Among the positive electrode materials for sodium ion batteries, the O3 structure positive electrode material has a higher initial sodium content, so the gram capacity is relatively high. However, there is a large amount of sodium hydroxide and sodium carbonate on the surface of the existing O3 structure sodium ion battery positive electrode material particles, which will react with the electrolyte, especially in the slurry preparation process, and gelation will occur. Although part of the above-mentioned residual alkali can be removed by washing with water, it increases the process and cost. Summary of the invention
[0005] The purpose of the present application is to provide a sodium ion battery positive electrode material and a preparation method thereof, a positive electrode plate, a sodium ion battery and electrical equipment, aiming to solve the problem that there is a large amount of residual alkali on the surface of the existing O3 structure positive electrode material particles.
[0006] To achieve the above objectives, the present application provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0007] The precursor and the sodium source are mixed and sintered to obtain a positive electrode material;
[0008] The positive electrode material is mixed with an organic acid and lithium hydroxide, and ground to obtain the positive electrode material for a sodium ion battery.
[0009] In some embodiments, at least one of the following conditions is met:
[0010] A. the organic acid is selected from one or more of citric acid, acetic acid, oxalic acid, oxalic acid, malonic acid, succinic acid, benzoic acid, and phenylacetic acid;
[0011] B. The mass of the organic acid is 0.001%-15% of the mass of the positive electrode material. Optionally, the mass of the organic acid is 0.2%-15% of the mass of the positive electrode material;
[0012] C. The mass of the lithium hydroxide is 0.5%-12% of the mass of the positive electrode material;
[0013] D. The particle size D50 of the lithium hydroxide is 1.0-5.0 μm.
[0014] In some embodiments, an organic solvent is added to the mixture of the positive electrode material, the organic acid and the lithium hydroxide, and the mass of the organic solvent is 1-2 times the mass of the organic acid.
[0015] In some embodiments, the grinding is ball milling and satisfies at least one of the following conditions:
[0016] A. The ball-to-material ratio is 2:(0.8-2.0);
[0017] B. The ball milling speed is 300-1000rpm;
[0018] C. Ball milling time is 1-5h;
[0019] D. After the grinding, the method further comprises: vacuum drying, wherein the vacuum drying temperature is 80-135° C. and the time is 0.5-4.5 hours.
[0020] In some embodiments, at least one of the following conditions is met:
[0021] A. The molar ratio of the metal cation in the precursor to the Na ion in the sodium source is 1:(0.95-1.4);
[0022] B. the sodium source is selected from one or more of sodium hydroxide, sodium carbonate, sodium oxalate and sodium citrate;
[0023] C. The sintering is carried out in an oxygen-containing atmosphere, and the flow rate of the oxygen-containing atmosphere is 2 to 20 mL / min;
[0024] D. The sintering includes: increasing the temperature from room temperature to 400-550°C at a heating rate of 2-5°C / min for pre-sintering for 4-8 hours, and then increasing the temperature to 800-1100°C at a heating rate of 2-5°C / min for sintering for 10-24 hours.
[0025] In some embodiments, the chemical formula of the precursor is: Ni x M (1-x) (OH)2, and the chemical formula of the positive electrode material for sodium-ion battery is: Na y Ni x M (1-x) O2, where 0 < x ≤ 1 and 0.9 ≤ y ≤ 1.05; M is one or more of Fe, Mn, Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, B, Sr, Ta.
[0026] This application also provides a positive electrode material for sodium-ion battery, which is prepared by the preparation method of the positive electrode material for sodium-ion battery described above.
[0027] This application also provides a positive electrode plate, which includes the positive electrode material for sodium-ion battery described above.
[0028] This application also provides a sodium-ion battery, which includes the positive electrode plate described above.
[0029] This application also provides an electricity-related device, which includes the sodium-ion battery described above.
[0030] Compared with the prior art, the beneficial effects of this application include:
[0031] The preparation method of the positive electrode material for sodium-ion battery provided by this application can in-situ generate a sodium supplement agent and excess water on the surface of the positive electrode material particles by using an organic acid to react with residual alkali. After this reaction ends, nanoscale lithium hydroxide particles dissolve in the generated water, and the lithium ions dissolved in the water will utilize the chemical potential difference between Li + and Na + to occur a liquid-phase ion exchange reaction, that is, Na + in the host structural material diffuses into the solution, while Li + with the same charge in the solution diffuses into the main lattice. By introducing a trace amount of Li element into the sodium layer on the particle surface through this method, the repulsive force generated by oxygen-oxygen between the positive electrode materials in the high state of charge (SOC) can be alleviated. This repulsive force will cause a ladder-shaped slip of the transition metal layer, and the exposed slip plane will further react with the electrolyte to generate a CEI film. After introducing lithium, this slip phenomenon can be inhibited to a certain extent, thereby improving the structural stability and electrochemical performance of the positive electrode material.
[0032] The positive electrode material for sodium-ion battery provided by this application can not only supplement the active sodium source consumed by the continuous generation of SEI film during the cycle of the sodium-ion battery, but also reduce the repulsive force caused by the vacancies generated after the sodium ions are removed, and maintain the integrity of the material structure.
[0033] The present application provides positive electrode sheets, sodium ion batteries and electrical equipment having excellent electrochemical properties due to the use of the sodium ion battery positive electrode materials of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0035] Figure 1 This is a schematic diagram of the process of preparing the positive electrode material for a sodium ion battery of the present application. DETAILED DESCRIPTION
[0036] As used herein:
[0037] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0038] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0039] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0040] In these examples, parts and percentages are by mass unless otherwise indicated.
[0041] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0042] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0043] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0044] This application provides a method for preparing a positive electrode material for a sodium ion battery. Figure 1 ,include:
[0045] S100: mixing and sintering the precursor and the sodium source to obtain a positive electrode material;
[0046] S200: mixing and grinding the positive electrode material with an organic acid and lithium hydroxide to obtain a positive electrode material for a sodium ion battery.
[0047] The preparation method of the positive electrode material of the sodium ion battery provided in the present application can generate a sodium supplement and excess water in situ on the surface of the positive electrode material particles by reacting an organic acid with a residual alkali. After the reaction is completed, the nano-scale lithium hydroxide particles dissolve in the generated water, and the lithium ions dissolved in the water utilize Li + with Na + The chemical potential difference between them causes a liquid phase ion exchange reaction, that is, the Na + Diffusion from the host lattice into the solution, and the Li + Then it diffuses into the main lattice. Introducing a trace amount of Li element into the sodium layer on the surface of the particle through this method can alleviate the repulsive force between oxygen and oxygen in the positive electrode material under high state of charge (SOC). This repulsive force will cause the transition metal layer to produce a ladder-like slip, and the exposed slip surface will further react with the electrolyte to form a CEI film. After the introduction of lithium, this slip phenomenon can be suppressed to a certain extent, thereby improving the structural stability and electrochemical performance of the positive electrode material.
[0048] In some embodiments, the organic acid in step S200 is selected from one or more of citric acid, acetic acid, oxalic acid, oxalic acid, malonic acid, succinic acid, benzoic acid, and phenylacetic acid.
[0049] In some embodiments, the mass of the organic acid in step S200 is 0.001%-15% of the mass of the positive electrode material, for example, it can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value between 0.001%-15%.
[0050] Optionally, the mass of the organic acid is 0.2%-15% of the mass of the positive electrode material.
[0051] Optionally, the mass of the organic acid is 1%-10% of the mass of the positive electrode material.
[0052] In some embodiments, the mass of lithium hydroxide in step S200 is 0.5%-12% of the mass of the positive electrode material, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or any value between 0.5% and 12%.
[0053] In some embodiments, in step S200, an organic solvent is added to the mixture of the positive electrode material, the organic acid and the lithium hydroxide, and the mass of the organic solvent is 1-2 times the mass of the organic acid, for example, it can be 1 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times or 2 times.
[0054] In some embodiments, the grinding in step S200 is ball milling, and the ball-to-material ratio is 2:(0.8-2.0), for example, it can be any ratio between 2:0.8, 2:1.0, 2:1.2, 2:1.4, 2:1.6, 2:1.8, 2:2.0 or 2:(0.8-2.0); the ball milling speed is 300-1000rpm, for example, it can be 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm or any value between 300-1000rpm; the ball milling time is 1-5h, for example, it can be 1h, 2h, 3h, 4h, 5h or any value between 1-5h.
[0055] The grinding and mixing in step S200 can evenly disperse the organic acid and lithium hydroxide, and this process can reduce the particle size of the organic acid and lithium hydroxide, which is more conducive to the progress of the reaction. If the cathode material, organic acid, and lithium hydroxide are directly heated without grinding and mixing, water removal will occur, which is not conducive to the ion exchange reaction.
[0056] In some embodiments, after the grinding in step S200, it further includes: vacuum drying, the temperature of the vacuum drying is 80 - 135 °C, for example, it can be 80 °C, 85 °C, 90 °C, 95 °C, 100 °C, 105 °C, 110 °C, 115 °C, 120 °C, 125 °C, 130 °C, 135 °C or any value between 80 - 135 °C, and the time is 0.5 - 4.5 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 4.5 h or any value between 0.5 - 4.5 h.
[0057] In some embodiments, the chemical formula of the precursor in step S100 is: Ni x M (1-x) (OH)2, and the chemical formula of the cathode material is: Na y Ni x M (1-x) O2, 0 < x ≤ 1, 0.9 ≤ y ≤ 1.05; M is one or more of Fe, Mn, Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, B, Sr, Ta.
[0058] Among them, the precursor can be obtained by adding ammonia water and sodium hydroxide for neutralization to a soluble metal salt solution, generating a precipitate through the co - precipitation method, and then filtering, washing the precipitate, and drying it at 100 - 300 °C for 2 - 6 hours.
[0059] In some embodiments, the molar ratio of the metal cations in the precursor to the Na ions in the sodium source is 1:(0.95 - 1.4), for example, it can be 1:0.95, or 1:0.98, or 1:1.0, or 1:1.2, or 1:1.4; the sodium source is selected from one or more of sodium hydroxide, sodium carbonate, sodium oxalate, and sodium citrate.
[0060] In some embodiments, the sintering in step S100 is carried out in an oxygen - containing atmosphere, for example, it can be an air atmosphere or an oxygen atmosphere, and the flow rate of the oxygen - containing atmosphere is 2 - 20 mL / min, for example, it can be 2 mL / min, 5 mL / min, 8 mL / min, 10 mL / min, 15 mL / min, 20 mL / min or any value between 2 - 20 mL / min.
[0061] In some embodiments, the sintering in step S100 includes: increasing the temperature from room temperature to 400-550°C (for example, 400°C, 450°C, 500°C or 550°C) at a heating rate of 2-5°C / min (for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min), performing pre-sintering for 4-8h (for example, 4h, 5h, 6h, 7h or 8h), and then further increasing the temperature to 800-1100°C (for example, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C) at a heating rate of 2-5°C / min (for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min), and sintering for 10-24h (for example, 10h, 12h, 15h, 18h, 20h or 24h).
[0062] The present application also provides a sodium ion battery positive electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery positive electrode material.
[0063] The sodium ion battery positive electrode material provided in the present application can not only replenish the active sodium source consumed by the sodium ion battery in the continuous generation of the CEI membrane during the cycle process, but also reduce the repulsive force caused by the vacancies generated after the sodium ions escape, thereby maintaining the integrity of the material structure.
[0064] The morphology of the positive electrode material of the sodium ion battery is a single crystal particle. After the lithium ions and sodium ions are exchanged, a trace amount of lithium doping exists on the surface of the positive electrode material, and the depth is 0.2-3nm at the interface of the positive electrode material particles.
[0065] The present application also provides a positive electrode plate, comprising the above-mentioned sodium ion battery positive electrode material.
[0066] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode plate.
[0067] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0068] The present application provides positive electrode sheets, sodium ion batteries and electrical equipment having excellent electrochemical properties due to the use of the sodium ion battery positive electrode materials of the present application.
[0069] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0070] Example 1
[0071] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0072] (1) Nickel salt (NiSO4·6H2O), iron salt (FeSO4·7H2O), manganese salt (MnSO4·H2O), and aluminum salt Al2(SO4)3·18H2O are dissolved in deionized water and mixed evenly to prepare a soluble salt solution with a total metal ion concentration of 2 mol / L, wherein the corresponding nickel salt, iron salt, manganese salt, and aluminum salt are weighed according to a molar ratio of Ni:Fe:Mn:Al=40:20:35:5. Then, the above-mentioned soluble salt solution, 8 mol / L NaOH solution, and 10 mol / L NH3·H2O complexing agent solution were transferred to a continuous stirred tank reactor in parallel, and nitrogen with a purity of 99.5% was introduced. The stirring device of the continuous stirred tank reactor was turned on, and the temperature of the continuous stirred tank reactor was controlled at 50°C. The pH value of the reaction system was continuously monitored during the reaction process, and the pH value of the reaction system was adjusted to 10.8-11.9. The reaction was continued for 48 hours, and the reaction was stopped when the average particle size reached 6.0-6.5 μm. Finally, the precursor was filtered and washed and dried at 150°C for 5 hours to obtain the final precursor product Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2.
[0073] (2) The hydroxide precursor Ni obtained in step (1) 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased from room temperature to 400°C at a heating rate of 3°C / min for 8h of pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased from 400°C to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 101 Ni 04 Fe 02 Mn 035 Al 005 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0074] (3) The positive electrode material Na obtained in step (2) 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05O2 is mixed with citric acid and lithium hydroxide in a mass ratio of 1:0.02:0.01, and then ethanol is added in a ratio of citric acid to ethanol of 1:1.5 by weight. The mixture is added to a ball mill and ball milled at a ball-to-material ratio of 2:1.2 at a rotation speed of 300-1000 rpm for 3 hours.
[0075] (4) The material obtained in step (3) is vacuum dried at a temperature of 105° C. for 2 h to obtain the sodium ion battery positive electrode material of Example 1.
[0076] Example 2
[0077] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0078] (1) The difference from Example 1 is that the nickel sulfate / manganese sulfate / ferric sulfate solution and titanium sulfate are mixed uniformly according to the molar ratio of Ni:Fe:Mn:Ti=30:20:45:5 to obtain a soluble salt solution with a total metal ion concentration of 2 mol / L. The other steps are the same as those in Example 1 to obtain a hydroxide precursor Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05 (OH)2.
[0079] (2) The hydroxide precursor Ni obtained in step (1) 0.3 Fe 0.2 Mn 0.45 Ti 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased from room temperature to 400°C at a heating rate of 3°C / min for 8h of pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased from 400°C to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0080] (3) The positive electrode material Na obtained in step (2) 1.01 Ni 0.3 Fe 0.2 Mn 0.45 Ti 0.05O2 is mixed with acetic acid and lithium hydroxide in a mass ratio of 1:0.03:0.05, and then ethanol is added in a ratio of acetic acid to ethanol of 1:1.4 by weight. The mixture is added to a ball mill and ball-milled at a ball-to-material ratio of 2:1.2 at a rotation speed of 300-1000 rpm for 3 hours.
[0081] (4) The material obtained in step (3) was vacuum dried at a temperature of 105° C. for 2 h to obtain the sodium ion battery positive electrode material of Example 2.
[0082] Example 3
[0083] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0084] (1) The difference from Example 1 is that nickel sulfate / manganese sulfate / ferric sulfate solution / aluminum sulfate and copper sulfate solution are mixed uniformly according to the molar ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a soluble salt solution with a total metal ion concentration of 2 mol / L. The other steps are the same as those in Example 1 to obtain a hydroxide precursor Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2.
[0085] (2) The hydroxide precursor Ni obtained in step (1) 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased from room temperature to 400°C at a heating rate of 3°C / min for 8h of pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased from 400°C to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0086] (3) The positive electrode material Na obtained in step (2) 1.01 Ni 0.35 Fe 0.2 Mn0.35 Cu 0.05 Al 0.05 O2 is mixed with citric acid, acetic acid, oxalic acid, oxalic acid and malonic acid in a total mass ratio of 1:0.05, wherein the mass ratio of citric acid, acetic acid, oxalic acid, oxalic acid and malonic acid is 1:1:1:1:1, and the mass ratio of lithium hydroxide to the positive electrode material is 0.07:1. Ethanol is then added in a ratio of acid to ethanol of 1:1.3. The mixture is added to a ball mill and ball milled at a ball-to-material ratio of 2:1.2 at a rotation speed of 300-1000rpm for 3 hours.
[0087] (4) The material obtained in step (3) was vacuum dried at a temperature of 105° C. for 2 h to obtain the sodium ion battery positive electrode material of Example 3.
[0088] Example 4
[0089] The difference between Example 4 and Example 1 is that the grinding method in step (3) is dry grinding, and no organic solvent ethanol is added to obtain the sodium ion battery positive electrode material of Example 4.
[0090] Example 5
[0091] The difference between Example 5 and Example 1 is that in step (3), the positive electrode material is mixed with citric acid and lithium hydroxide in a mass ratio of 1:0.04:0.07 to obtain the sodium ion battery positive electrode material of Example 5.
[0092] Example 6
[0093] The difference between Example 6 and Example 1 is that citric acid and benzoic acid are used in step (3), the mass ratio of the total mass of citric acid and benzoic acid to the positive electrode material is 0.04:1, wherein the mass ratio of citric acid and benzoic acid is 1:1, and the mass ratio of lithium hydroxide to the positive electrode material is 0.09:1, thereby obtaining the sodium ion battery positive electrode material of Example 6.
[0094] Example 7
[0095] The difference between Example 7 and Example 1 is that citric acid and phenylacetic acid are used in step (3), the mass ratio of the total mass of citric acid and phenylacetic acid to the positive electrode material is 0.04:1, wherein the mass ratio of citric acid to phenylacetic acid is 1:1, and the mass ratio of lithium hydroxide to the positive electrode material is 0.09:1, thereby obtaining the sodium ion battery positive electrode material of Example 7.
[0096] Example 8
[0097] The difference between Example 8 and Example 1 is that: citric acid and succinic acid are used in step (3), the mass ratio of the total mass of citric acid and succinic acid to the positive electrode material is 0.05:1, wherein the mass ratio of citric acid and succinic acid is 1:1, and the mass ratio of lithium hydroxide to the positive electrode material is 0.09:1, thereby obtaining the sodium ion battery positive electrode material of Example 8.
[0098] Comparative Example 1
[0099] Comparative Example 1 is different from Example 1 in that there are no steps (3) and (4), and the positive electrode material Na obtained in step (2) is directly 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 O2 is used as the positive electrode material of the sodium ion battery in Comparative Example 1.
[0100] Comparative Example 2
[0101] Comparative Example 2 is different from Example 2 in that there are no steps (3) and (4), and the positive electrode material Na obtained in step (2) is directly 101 Ni 03 Fe 02 Mn 045 Ti 005 O2 is used as the positive electrode material of the sodium ion battery in Comparative Example 2.
[0102] Comparative Example 3
[0103] Comparative Example 3 is different from Example 3 in that there are no steps (3) and (4), and the positive electrode material Na obtained in step (2) is directly 1.01 Ni 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2 is used as the positive electrode material of the sodium ion battery in Comparative Example 3.
[0104] Comparative Example 4
[0105] The difference between Comparative Example 4 and Example 8 is that no lithium hydroxide is added for grinding in step (3) to obtain the sodium ion battery positive electrode material of Comparative Example 4.
[0106] Comparative Example 5
[0107] The difference between Comparative Example 5 and Example 7 is that the positive electrode material, citric acid, phenylacetic acid, and lithium hydroxide materials mixed evenly in step (3) are placed in an oven at 85° C. and baked for 2 h to obtain the sodium ion battery positive electrode material of Comparative Example 5.
[0108] The sodium ion battery positive electrode materials prepared in the above-mentioned embodiments and comparative examples are mixed according to the positive electrode sheet formula: the mass ratio of positive electrode active material, conductive carbon black, conductive carbon tube, polyvinylidene fluoride and N-methylpyrrolidone is 96.5:1:0.5:2:40, and the mixture is stirred at 500rpm for 4h to obtain sodium positive electrode material slurry. The prepared positive electrode slurry is evenly coated on aluminum foil with a scraper, placed in a blast drying oven, and dried at 120°C for 20min. Finally, the dried electrode sheet is rolled and cut to make a positive electrode sheet. The obtained positive electrode sheet, the negative electrode prepared from hard carbon and the diaphragm are assembled into a 1.3Ah soft-pack battery cell after winding, packaging and other processes. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate and dimethyl carbonate are evenly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coated film is selected as a diaphragm.
[0109] Battery performance test:
[0110] Constant capacity test: The 1.3Ah soft-pack battery cell prepared by the above method was charged for the first time at a rate of 0.05C in the voltage range of 1.5-4.0V. When charged to 4.0V, constant voltage charging was performed with a cut-off current of 0.02C. Then, 0.33C discharge was performed until the cut-off current was 1.5V, and the first charge and discharge capacity was tested.
[0111] pH paper strip method to test pH: by immersing the reagent in the liquid to be tested, and then reading the pH value according to the color change of the paper strip coated with the reagent.
[0112] Gas production test: The test battery with 100% SOC was stored at 70°C for 30 days. The battery volume was measured every 7 days and recharged to 100% SOC. The final rate of change of the battery volume was the measured gas production rate.
[0113] Cyclic performance test: At 25°C and in the range of 1.5-4.0V, charge at a rate of 0.5C with a cut-off current of 0.05C, then discharge at a rate of 1C to the lower limit voltage, and cycle 100 times.
[0114] The electrochemical properties of the sodium ion battery positive electrode materials of various embodiments and comparative examples are shown in Table 1.
[0115] Table 1 Electrochemical properties of sodium ion battery positive electrode materials of various embodiments and comparative examples
[0116]
[0117]
[0118] As can be seen from Table 1, in Examples 1 to 8 and Comparative Examples 4 and 5, the pH value of the positive electrode material obtained by adding organic acid is significantly reduced, and the first efficiency of the whole battery is significantly higher than that of Comparative Examples 1 to 3, indicating that the sodium supplement formed by the positive electrode material treated with organic acid replenishes the sodium source consumed in the formation of the SEI film, and the corresponding gas production of the sodium ion battery during high-temperature storage is also reduced, and the lithium ions entering the lattice make the material have better cycle performance.
[0119] Since no lithium hydroxide was added to Comparative Example 4, the capacity retention rate after 100 cycles was significantly lower than that of the embodiment. Although organic acid and lithium hydroxide were added to Comparative Example 5, the mixed material was not ground but directly heated, and the first efficiency and capacity retention rate of the obtained positive electrode material were lower than those of the embodiment.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0121] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: include: The precursor and the sodium source are mixed and sintered to obtain a positive electrode material; The positive electrode material is mixed with an organic acid and lithium hydroxide, and ground to obtain the positive electrode material for a sodium ion battery.
2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. the organic acid is selected from one or more of citric acid, acetic acid, oxalic acid, oxalic acid, malonic acid, succinic acid, benzoic acid, and phenylacetic acid; B. The mass of the organic acid is 0.001%-15% of the mass of the positive electrode material. Optionally, the mass of the organic acid is 0.2%-15% of the mass of the positive electrode material; C. The mass of the lithium hydroxide is 0.5%-12% of the mass of the positive electrode material; D. The particle size D50 of the lithium hydroxide is 1.0-5.0 μm.
3. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: An organic solvent is added to a mixture of the positive electrode material, the organic acid and the lithium hydroxide, and the mass of the organic solvent is 1 to 2 times the mass of the organic acid.
4. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The grinding is ball milling and satisfies at least one of the following conditions: A. The ball-to-material ratio is 2:(0.8-2.0); B. The ball milling speed is 300-1000rpm; C. Ball milling time is 1-5h; D. After the grinding, the method further comprises: vacuum drying, wherein the vacuum drying temperature is 80-135° C. and the time is 0.5-4.5 hours.
5. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: At least one of the following conditions is met: A. The molar ratio of the metal cation in the precursor to the Na ion in the sodium source is 1:(0.95-1.4); B. the sodium source is selected from one or more of sodium hydroxide, sodium carbonate, sodium oxalate and sodium citrate; C. The sintering is carried out in an oxygen-containing atmosphere, and the flow rate of the oxygen-containing atmosphere is 2 to 20 mL / min; D. The sintering includes: increasing the temperature from room temperature to 400-550°C at a heating rate of 2-5°C / min for pre-sintering for 4-8 hours, and then increasing the temperature to 800-1100°C at a heating rate of 2-5°C / min for sintering for 10-24 hours.
6. The method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 5, characterized in that: The chemical formula of the precursor is: Ni x M (1-x) (OH)2, and the chemical formula of the positive electrode material for the sodium ion battery is: Na y Ni x M (1-x) O2, where 0 < x ≤ 1 and 0.9 ≤ y ≤ 1.05; M is one or more of Fe, Mn, Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, B, Sr, Ta.
7. A sodium ion battery positive electrode material, characterized in that: The positive electrode material for a sodium ion battery is prepared by the method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 6.
8. A positive electrode sheet, characterized in that: Including the sodium ion battery positive electrode material according to claim 7.
9. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Cited By
A cathode active material for sodium batteries
WO2026202256A1